2020
DOI: 10.1016/j.isci.2020.101774
|View full text |Cite
|
Sign up to set email alerts
|

Single-Cell Transcriptome Analysis Dissects the Replicating Process of Pancreatic Beta Cells in Partial Pancreatectomy Model

Abstract: Summary Heterogeneity of gene expression and rarity of replication hamper molecular analysis of β-cell mass restoration in adult pancreas. Here, we show transcriptional dynamics in β-cell replication process by single-cell RNA sequencing of murine pancreas with or without partial pancreatectomy. We observed heterogeneity of Ins1 -expressing β-cells and identified the one cluster as replicating β-cells with high expression of cell proliferation markers Pcna … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 55 publications
3
16
0
Order By: Relevance
“…The current study reveals the cellular dynamics of the regenerating pancreas after surgical resection. It resonates some of the observations reporter by Tatsuoka et al (2020), were self-duplicating beta-cells were observed following partial pancreatectomy. Our work further enables a new look into beta-cell heterogeneity following regeneration and physically interacting endocrine cells, which were overlooked until the recent development of computational methods for discrimination of true interactions from sorting doublet artifacts.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The current study reveals the cellular dynamics of the regenerating pancreas after surgical resection. It resonates some of the observations reporter by Tatsuoka et al (2020), were self-duplicating beta-cells were observed following partial pancreatectomy. Our work further enables a new look into beta-cell heterogeneity following regeneration and physically interacting endocrine cells, which were overlooked until the recent development of computational methods for discrimination of true interactions from sorting doublet artifacts.…”
Section: Discussionsupporting
confidence: 86%
“…Beta cells re-enter the cell division cycle in the regenerating pancreas, peaking at the first week after injury (Ackermann Misfeldt et al, 2008; Dor et al, 2004; Teta et al, 2007; Togashi et al, 2014) and were recently suggested to be associated with intricate activation of stress response, cell cycle progression effectors and tumor suppressors (Tatsuoka et al, 2020). Our analysis reveals a residual replicating beta cells, even 4 weeks following surgery, indicative of a prolonged replication phase than previously appreciated (Togashi et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To demonstrate the effectiveness of our distance metric when applied in a gene clustering algorithm, we compare our algorithm to four other methods (k-means, hierarchical clustering, principal component analysis, and Clust, all of which have yielded strong results in previous work [15,16,23,8]) by running the resulting clustered matrices through SC3, a cell clustering procedure [2]. In each dataset, we chose to use cell labels that represent distinct biological states or conditions [24][25][26][27][28][29][30][31][32][33]. Therefore, the cell labels are highly objective.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that .1,000 cell cycle-specific genes are not expressed in quiescent cells (3). b-cells induced to proliferate by c-Myc upregulation (4) or partial pancreatectomy (5) show decreased expression of many b-cell lineage identity genes, including Pdx1, although b-cell identity genes may be longer lived, and some can still be detected in proliferating cells (6,7). Likewise, gene expression analyses of sorted proliferating b-cells from transgenic mice expressing GFP in cycling cells revealed decreased expression of genes involved in b-cell function (8).…”
mentioning
confidence: 99%